Radiological assessment of facial recess and correlation with surgical measurement in cochlear implantation - Essam Abdel Wanees Behairy; Mohamed Hisham Hamad; Mohamed Shawky; Sohair Reda Aboshady; Ashraf Ali Eldemerdash (The Egyptian Journal of Otolaryngology, 2023)
Abstract Background The facial recess (FR) is the crucial landmark in posterior tympanotomy approach which is the conventional approach for cochlear implantation surgery. This work aimed to measure the facial recess width and length radiologically and correlate these measurements with the surgical measurements in cochlear implantation procedure. An observational cross-sectional study was conducted on one hundred patients with sensorineural hearing loss prepared for cochlear implantation according to health insurance regulations. Patients included in the study were subjected to the following protocol: a routine ENT examination formed the initial part of the evaluation, audiological tests for adults and children were done, and the radiological evaluation for the patients included high-resolution computed tomography (HRCT) scanning [axial plane, oblique sagittal plane, and curved multiplanar reconstruction (MPR CT)]. These HRCT images were used to measure the facial recess width and length. Measurement of the FR width and length was done intraoperative by using a sterile ruler. Radiological measurements were correlated with the surgical measurements. Results There was a statistically significant correlation between FR width surgically and FR width radiologically (p-value < 0.001). FR width measured in CT axial cuts, curved MPR images, and oblique sagittal cuts could predict FR width surgically. There was a statistically significant correlation between FR length surgically and FR length radiologically (p-value < 0.001). There was no statistically significant correlation between age and sex on one hand and surgical and radiological measurements on the other hand. Conclusion Preoperative HRCT axial plane, oblique sagittal plane, and curved MPR CT can predict actual facial recess width and length.